2020
DOI: 10.1111/bju.14765
|View full text |Cite
|
Sign up to set email alerts
|

The status and characteristics of urinary stone composition in China

Abstract: Epidemiology ObjectivesTo explore characteristics of urinary stone composition in China, and determine the effects of gender, age, body mass index (BMI), stone location, and geographical region on stone composition. Patients and methodsWe prospectively used Fourier-transform infrared spectroscopy to analyse stones from consecutive patients presenting with new-onset urolithiasis at 46 hospitals in seven geographical areas of China, between 1 June 2010 and 31 May 2015. Chi-squared tests and logistic regression a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
57
4
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 77 publications
(68 citation statements)
references
References 31 publications
6
57
4
1
Order By: Relevance
“…As a regional centre for stone treatment, our centre dealt with more complex cases of staghorn calculi and urinary calculi with severe infections, which could lead to a selection bias. Consistent with the results in other reports 2,5,7,8,10,12 , we found that the proportion of infection stones among females in the present study was three times that in males, accounting for 15.5% and 3.9%, respectively. Another finding of our research was that the rate of infection stone is apparently related to urinary tract infection and a higher urine pH profile.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…As a regional centre for stone treatment, our centre dealt with more complex cases of staghorn calculi and urinary calculi with severe infections, which could lead to a selection bias. Consistent with the results in other reports 2,5,7,8,10,12 , we found that the proportion of infection stones among females in the present study was three times that in males, accounting for 15.5% and 3.9%, respectively. Another finding of our research was that the rate of infection stone is apparently related to urinary tract infection and a higher urine pH profile.…”
Section: Discussionsupporting
confidence: 93%
“…Our study reveals that the urinary stone composition in central China has its www.nature.com/scientificreports/ own characteristics compared with those in other areas in China, which is highly correlated with sex, age, stone location, clinical biochemical indexes and geographic location. In our study, the prevalence of CaOx (78.37% of stones) was higher than that in other regions in China 2,5,8,12,13 . The mainly vegetarian diet in central China may lead to this high CaOx prevalence.…”
Section: Discussioncontrasting
confidence: 56%
See 2 more Smart Citations
“…In addition, kidney stones have a high occurrence rate (2). calcium oxalate (caOx)-induced kidney stones, which are the most common types of kidney stones, account for approximately 60% of all cases of kidney stones in china (3). caOx-induced kidney stones can be formed by crystal deposits in tubular epithelial cells, a high level of reactive oxygen species (ROS) and the subsequent inflammatory response.…”
Section: Introductionmentioning
confidence: 99%